Maturation of pre‐40S particles in yeast and humans. (8th November 2018) - Cerezo, Emilie; Plisson‐Chastang, Célia; Henras, Anthony K.; Lebaron, Simon; Gleizes, Pierre‐Emmanuel; O'Donohue, Marie‐Françoise; Romeo, Yves; Henry, Yves
Abstract : The synthesis of ribosomal subunits in eukaryotes requires the interplay of numerous maturation and assembly factors (AFs) that intervene in the insertion of ribosomal proteins within pre‐ribosomal particles, the ribosomal subunit precursors, as well as in pre‐ribosomal RNA (rRNA) processing and folding. Here, we review the intricate nuclear and cytoplasmic maturation steps of pre‐40S particles, the precursors to the small ribosomal subunits, in both yeast and human cells, with particular emphasis on the timing and mechanisms of AF association with and dissociation from pre‐40S particles and the roles of these AFs in the maturation process. We highlight the particularly complex pre‐rRNA processing pathway in human cells, compared to yeast, to generate the mature 18S rRNA. We discuss the information gained from the recently published cryo‐electron microscopy atomic models of yeast and human pre‐40S particles, as well as the checkpoint/quality control systems that seem to operate to probe functional sites within yeast cytoplasmic pre‐40S particles. This article is categorized under: RNA Processing > rRNA Processing Translation > Ribosome Biogenesis Abstract : Production of the small ribosomal subunit in eukaryotes involves the co‐transcriptional assembly of an initial pre‐ribosomal particle containing a subset of ribosomal proteins (RPs) as well as assembly and maturation factors (AFs). This initial pre‐ribosomal particle is split into pre‐40S and pre‐60S pre‐ribosomal particles that follow independent maturation pathways. This review deals with pre‐40S particle maturation only. The nuclear pre‐40S particles are exported via the nuclear pores into the cytoplasm. There, the AFs that function in RP recruitment and control ribosomal RNA (rRNA) folding are sequentially removed. In addition, in yeast at least, cytoplasmic pre‐40S particles are submitted to a quality control process involving a transient interaction with a 60S ribosomal subunit. At the end of the maturation pathway, 18S rRNA is released by an endonucleolytic cleavage.